2001
DOI: 10.1002/jgm.192
|View full text |Cite
|
Sign up to set email alerts
|

Triplex-forming molecules: from concepts to applications

Abstract: The ability to specifically manipulate gene expression has wide-ranging applications in experimental biology and in gene-based therapeutics. The design of molecules that recognise specific sequences on the DNA double helix provides us with interesting tools to interfere with DNA information processing at an early stage of gene expression. Triplex-forming molecules specifically recognise oligopyrimidine-oligopurine sequences by hydrogen bonding interactions. Applications of such triplex-forming molecules (TFMs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 95 publications
1
52
0
Order By: Relevance
“…psoriasis. The present findings support the possibility that triplex-forming oligonucleotides together with other high affinity specific DNA-binding molecules, such as peptide nucleic acids and polyamides (16), may prove useful for the development of therapeutics and as tools for further understanding of DNA-associated functions in the cellular context.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…psoriasis. The present findings support the possibility that triplex-forming oligonucleotides together with other high affinity specific DNA-binding molecules, such as peptide nucleic acids and polyamides (16), may prove useful for the development of therapeutics and as tools for further understanding of DNA-associated functions in the cellular context.…”
Section: Discussionsupporting
confidence: 79%
“…A number of studies have reported TFO-associated activities in cell culture experiments including the modulation of gene expression and the induction of genomic modifications at selected sites (16). Triplex-mediated inhibition of transcription may be achieved by interfering with transcription initiation (competition of TFOs with transcription factors at the promoter) or by interfering with transcription elongation (RNA synthesis arrest at triplex structures).…”
mentioning
confidence: 99%
“…[9,10] TFOs are easily customizable and have a large library of potential target sites in mammalian genomes. [11] Parallel or antiparallel triplexes can be formed via Hoogsteen, or reverse-Hoogsteen hydrogen bonds, respectively, depending on the orientation of the TFOs relative to the homopurine strand.…”
Section: Introductionmentioning
confidence: 99%
“…131 Longer binding-site size is considered to be crucial for application in gene regulation since longer sequences should occur less frequently in genome leading to the development of various polyamide motifs for selective targeting. 132,133 The most promising strategy came from chemical ligation of two hairpin polyamides to form dimers. 134,135 However, though having an excellent affinity and specificity to 10 base pair (bp) DNA sequences, hairpin dimers lack the cell and nuclear uptake properties of smaller hairpins, apparently due to size and shape.…”
Section: Dna Minor Groove Templation Rolementioning
confidence: 99%